2022
DOI: 10.3389/fendo.2022.946504
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of molecular features of PCOS with different androgen levels and immune-related prognostic biomarkers associated with implantation failure

Abstract: BackgroundPolycystic ovary syndrome (PCOS), the most common heterogeneous reproductive disease afflicting women of childbearing age, has been recognized as a chronic inflammatory disease recently. Most PCOS patients have hyperandrogenism, indicating a poor prognosis and poor pregnancy outcomes. The molecular mechanism underlying PCOS development is still unknown. In the present study, we investigated the gene expression profiling characteristics of PCOS with hyperandrogenism (HA) or without hyperandrogenism (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Consistent with previous studies ( 48 , 49 ), our data showed that the common gene population mainly enriched in the activation pathways of immune cells like T cells, NK cells, macrophages, and neutrophils. These results hinted us the high level of immunity in PCOS and RIF patients and prompted us to further investigate which immune cells are abnormal in the two diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies ( 48 , 49 ), our data showed that the common gene population mainly enriched in the activation pathways of immune cells like T cells, NK cells, macrophages, and neutrophils. These results hinted us the high level of immunity in PCOS and RIF patients and prompted us to further investigate which immune cells are abnormal in the two diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have stated that hormone abnormalities in PCOS can overstimulate the immune system, and concurrently, inflammatory cell infiltration aggravates ovarian dysfunction and metabolic disorders [ 35 , 36 ]. High infiltrating abundances of macrophages [ 37 ], neutrophils, activated dendritic cells [ 38 ], and eosinophils [ 39 , 40 ] were observed in PCOS. Since chronic low-level inflammation plays a critical role in PCOS [ 41 ], we investigated and compared the immune infiltration and cytokine levels in different groups.…”
Section: Discussionmentioning
confidence: 99%
“…The true predisposing factors for OSA in women with PCOS may be IR and obesity (152). Obesity/insulin-resistance may be the main cause of sleep apnea, which in turn may accelerate these metabolic abnormalities because of the gradual rise of cytokines, such as IL-6 and TNF-a (159).…”
Section: Pcos-related Immune Dysregulation In the Other Systemmentioning
confidence: 99%